Inflammatory markers and pulmonary function in adolescents and young adults 6 months after mild COVID-19 - Sommen, Silke Lauren; Havdal, Lise Beier; Selvakumar, Joel; Einvik, Gunnar; Leegaard, Truls Michael; Lund-Johansen, Fridtjof; Michelsen, Annika E.; Mollnes, Tom E.; Stiansen-Sonerud, Tonje; Tjade, Trygve; Wyller, Vegard Bruun Bratholm; Berven, Lise Lund (Frontiers in Immunology, 2023)
Introduction Both public and scientific attention have shifted from the acute COVID-19 illness to the chronic disability experienced by a proportion of COVID-19 convalescents. Post COVID-19 condition, a term used for long-lasting symptoms after COVID-19, can affect individuals across all disease severity and age groups. Data on post-COVID-19 symptomatology, epidemiology and pathophysiology in adolescents and young adults are scarce. To date, little is known on the immunological and pulmonary trends in these patients after COVID-19. This study investigated immunological markers and pulmonary function in non-hospitalized patients in this group at 6 months after initial mild COVID-19 infection. Methods Non-hospitalized SARS-CoV-2 positive (n = 405) and SARS-CoV-2 negative (n = 111) adolescents and young adults (aged 12-25 years) were followed prospectively for six months after SARS-CoV-2 PCR testing. At baseline and at six months follow-up, all participants underwent an assessment including clinical examination, questionnaires, spirometry, and blood sampling. Cross-sectional comparisons of blood biomarkers; including white blood cell counts, CRP, GDF-15, a 27-multiplex cytokine assay, complement activation products and SARS-CoV-2 antibodies; and spirometry measures were performed after classification of all participants according to their COVID-19 status and adherence to post-COVID-19 case criteria. Associations between biomarkers and COVID-19 symptoms were explored. Results No difference in pulmonary function was detected between the groups. COVID-19 convalescents had higher levels of chemokines eotaxin, MCP-1 and IP-10 than non-infected controls. The increase was modest and not associated with long-lasting COVID-19 symptoms. Discussion Elevated inflammatory mediators were found in adolescents and young adults six months after mild COVID-19, but there was no association with post-COVID-19 condition.